Divided attention during cutting influences lower extremity mechanics in female athletes - Almonroeder, T. G.; Kernozek, T.; Cobb, S.; Slavens, B.; Wang, J.; Huddleston, W. (Sports Biomechanics, 2019)
Anterior cruciate ligament (ACL) injuries in basketball appear to be more common when players are in possession of the ball. The greater risk of ACL injury when in possession of the ball may result from the athlete`s inability to fully attend to their movement. However, it is also possible that having to carry/manipulate the ball restricts the athlete`s ability to utilise their upper extremities for stability during a manoeuvre. The purpose of this study was to explore how possession of a basketball and divided attention influence lower extremity mechanics during cutting and landing. Twenty uninjured females with basketball experience performed a baseline lateral cutting task, as well as lateral cuts while carrying a basketball, with and without a subsequent chest pass. Requiring participants to carry the basketball in isolation (i.e., without the additional pass) had minimal influence on lower extremity mechanics compared to baseline. However, participants demonstrated less knee flexion (40.9° vs. 47.3°) and greater knee abduction (12.2° vs. 10.1°) for trials that included the additional pass (divided attention condition) compared to trials conducted while carrying the basketball in isolation. Athletes may be at greater risk for ACL injury when they are unable to solely attend to their movement.